Optimal I-V Curve Scan Time of Solar Cells and Modules in Light of Irradiance Level. (6th December 2012) - Herman, Matic; Jankovec, Marko; Topič, Marko
Abstract : High-efficiency solar cells and modules exhibit strong capacitive character resulting in limited speed of transient responses. A too fast I-V curve measurement can thus introduce a significant error due to its internal capacitances. This paper analyses the I-V curve error of a measured solar cell or module in light of scan time and irradiance level. It rests on a two-diode solar cell model extended by two bias-dependent capacitances, modelling the junction, and the diffusion capacitance. A method for determination of all extended model parameters from a quasistatic I-V curve and open-circuit voltage decay measurement is presented and validated. Applicability of the extended model and the developed parameter extraction method to PV modules is demonstrated and confirmed. SPICE simulations of the extended model are used to obtain the I-V curve error versus scan time dependence and the I-V curve hysteresis. Determination of the optimal scan time is addressed, and finally the influence of the irradiance level on the I-V curve scan time and error is revealed. The method is applied but is not limited to three different wafer-based silicon solar cell types.